О ПОЛИФУНКЦИОНАЛНОЈ ПРИРОДИ РЕЧИ ИНАЧЕ И ЊЕНИМ ФРАНЦУСКИМ ПРЕВОДНИМ ЕКВИВАЛЕНТИМА - Васиљевић, Анђела Д. (Journal for Languages & Literatures of the Faculty of Philosophy in Novi Sad / Zbornik za Jezike i Knjizevnosti Filozofskog Fakulteta u Novom Sadu, 2025)
The present paper explores the semantic-pragmatic and distribution features of the Serbian word inače 'otherwise' and its French equivalents. First, we provide an insight into its lexicographic treatment in Serbian general descriptive dictionaries, while also paying attention to some of the main issues related to the determination of its morphological and functional categories. Furthermore, we offer a brief review of the previous studies conducted on this question within the Serbian grammatical and pragmatic literature. The central part of the paper is devoted to the contrastive analysis of different occurrences of inače in comparison with its French translation possibilities. The equivalents are compared on morphosyntactic, semantic, pragmatic and stylistic levels. The aim of the research is to point out the existence of a wide range of values of the given word, an idiosyncratic lexeme which can function not only as an intra-predicative unit that modifies the verb, but also as an extra-predicative, topic-shift discourse marker. The analysis of the aligned examples suggests that the choice of French equivalents is highly conditioned by syntactic and pragmatic functions performed by inače in the source text, as well as by stylistic and register aspects of the latter.